Design, synthesis and biological evaluation of deuterated nintedanib for improving pharmacokinetic properties. (26th May 2015) - Xu, Ruixue; Zhan, Miao; Peng, Lingling; Pang, Xuehai; Yang, Jun; Zhang, Tao; Jiang, Hongxia; Zhao, Lifeng; Chen, Yuanwei
<x xml:space="preserve">Abstract</x> Nintedanib is a novel triple angiokinase inhibitor that inhibits three growth factors simultaneously. Deuterated derivatives of nintedanib at certain metabolically active sites were prepared and evaluated in vitro and in vivo. In particular, deuterated compound SKLB‐C2202 had significantly improved pharmacokinetic properties compared with nintedanib. These efforts lay the foundation for further investigating the druggability of SKLB‐C2202.